Book Reviews. (1st April 2018) - Berry-McCrea, Erin L.; Loviglio, Jason; Ruth, Nicolas
Word Warrior: Richard Durham, Radio, and Freedom, Sonja D. Williams (2015) Champaign, IL: University of Illinois Press, 272 pp., ISBN: 9780252081392, p/bk, $26.00; e-book, $23.40Performing Personality. On-Air Identities in a Changing Media Landscape, David Crider (2016) Lanham, MD.: Lexington Books, 204 pp., ISBN: 978 1 4985 3085 9, h/bk, $80.00, e-book $76.00